2016
DOI: 10.4038/cmj.v61i4.8380
|View full text |Cite
|
Sign up to set email alerts
|

Repetition rate after non-fatal self-poisoning in Sri-Lanka: a one year prospective longitudinal study

Abstract: Introduction Attempted or non-fatal self-poisoning is an important public health problem in Sri Lanka. Current evidence from Sri Lanka suggests that this phenomenon is more common among young people, and females, and is associated with a recent interpersonal conflict. International studies indicate that recent non-fatal selfharm is associated with an increased risk of repetition and completed suicide. Prospective follow-up data regarding rates of repetition of self-harm in Sri Lanka is limited.Objectives The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…Other possible reasons for the low prevalence of repeat self-harm in Asia are the lower prevalence of mental disorders among those who self-harm compared to levels seen in HICs 22 and longer inpatient stays helping individuals get through the period of greatest risk of repeat self-harm. Our estimates of a lower rate of self-harm repetition are consistent with previous estimates of repetition from south Asia,6, 8, 9, 10 but lower than the 12-month repetition rate from a prospective study from India (14%, 95% CI 10–19) 7 . Possible explanations for these differences might be differing methodology in the Indian study, including collection of data on self-reported self-harm, or differences in the socioeconomic and psychological health of our study population.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Other possible reasons for the low prevalence of repeat self-harm in Asia are the lower prevalence of mental disorders among those who self-harm compared to levels seen in HICs 22 and longer inpatient stays helping individuals get through the period of greatest risk of repeat self-harm. Our estimates of a lower rate of self-harm repetition are consistent with previous estimates of repetition from south Asia,6, 8, 9, 10 but lower than the 12-month repetition rate from a prospective study from India (14%, 95% CI 10–19) 7 . Possible explanations for these differences might be differing methodology in the Indian study, including collection of data on self-reported self-harm, or differences in the socioeconomic and psychological health of our study population.…”
Section: Discussionsupporting
confidence: 89%
“…There is, however, a paucity of evidence from LMICs in south Asia regarding the risk of suicide after a self-harm episode 2 . The few south Asian studies on this issue indicate that the risk of repeat self-harm is lower than in HICs,6, 7, 8, 9, 10 but there have been few prospective studies and most studies to date have been small and of low quality. A large prospective study 10 restricted to people who had self-poisoned in a rural region of Sri Lanka reported that the risk of repeat self-poisoning at 12 months was 5·7% (95% CI 5·0–6·4) and of suicide (all methods) at 2 years was 0·7% (0·4–0·9), considerably lower than the risks reported in HICs.…”
Section: Introductionmentioning
confidence: 99%
“…A telephone interview based study conducted at Teaching Hospital Peradeniya, Sri Lanka, reported recalled one year repetition rate, 2.7%. [15] Contextual and methodological differences partially explain these difference in rates.…”
Section: Discussionmentioning
confidence: 99%
“…The flow diagram for including studies could be seen in the Figure 1 . Of the included studies, 32 studies reported the associating factors of SH repetition, 7 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 21 studies reported the associating factors of suicide following SH, 11 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 and 9 studies both reported the associating factors of suicide and repetition following SH. 8 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83...…”
Section: Resultsmentioning
confidence: 99%